Դարձվածքները Ա. Բակունցի «Կյորես» վիպակում (համեմատական քննություն) - Քումունց, Մհեր; Բակունց, Ալլա (ՀՀ ԳԱԱ ԼԻ հրատ.)
As we know, idioms originate from various types of word combinations through resemanticization and the acquisition of figurative or metaphorical meanings. Most of the idioms in Aksel Bakunts’ works, being dialectal and commonly used in spoken language, require a different approach to their study. In this regard, the comparative method is the most effective. This involves comparing the idiom extracted from the text with its equivalent idiomatic unit found in the live speech of the Syunik-Artsakh dialectal region. The goal is to identify differences and similarities, as well as possible parallels in literary Armenian and its colloquial variants. Работы, посвященные фразеологизмам, достаточно многочисленны. Обычно встречаются исследования, связанные с фразеологической системой какого-либо автора, произведений, языка, литературного языка, лексики и фразеологического состава. В данном случае предметом нашего исследования являются фразеологизмы в произведениях Акселя Бакунца, имеющие диалектное происхождение и до сих пор нуждающиеся в освещении. Исследуемое произведение - «Кёрес» Акселя Бакунца, шедевр армянской литературы, в котором Бакунц использует фразеологизмы и диалект для выражения психологии персонажей, их социального положения и отражения действительности.
Keywords: Բարբառագիտություն